The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1105/tpc.001628
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Interaction between NPR1 and Transcription Factor TGA2 Leads to Salicylic Acid–Mediated Gene Activation in Arabidopsis

Abstract: The Arabidopsis NPR1 protein is a key regulator of salicylic acid (SA)-mediated gene expression in systemic acquired resistance. Based on yeast two-hybrid analysis, NPR1 has been suggested to interact with members of the TGA family of transcription factors, including TGA2 (AHBP-1b). However, genetic evidence demonstrating that the NPR1-TGA interaction occurs in planta is still lacking, and the role of this interaction in SA-mediated gene activation has yet to be determined. In this study, we expressed a trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
307
5
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(331 citation statements)
references
References 60 publications
11
307
5
3
Order By: Relevance
“…NPR1 is an SA-activated regulator of gene expression in SAR (Fan and Dong, 2002;Mou et al, 2003), and the growth patterns of npr1 mutants indicated that this component of SA signaling functions in chilling responses. The growth of chilled npr1 mutants was intermediate between wild-type and SA-deficient genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPR1 is an SA-activated regulator of gene expression in SAR (Fan and Dong, 2002;Mou et al, 2003), and the growth patterns of npr1 mutants indicated that this component of SA signaling functions in chilling responses. The growth of chilled npr1 mutants was intermediate between wild-type and SA-deficient genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It also displays reduced heat tolerance (Clarke et al, 2004). NPR1 accumulates in the nucleus in response to cellular redox changes and interacts with members of the TGA family of bZIP transcription factors (Després et al, 2000;Kinkema et al, 2000;Zhou et al, 2000;Fan and Dong, 2002;Mou et al, 2003). NPR1 is regarded as a key signal transducer functioning downstream of SA, but there are also SA-mediated NPR1-independent pathogen resistance responses (Bowling et al, 1997;Clarke et al, 2000).…”
mentioning
confidence: 99%
“…These interactions lead to the expression of NON-EXPRESSOR OF PR1 (NPR1) (Cao et al 1994;Delaney et al 1995;Glazebrook et al 1996;Shah et al 1997;Nawrath & Métraux 1999;Nawrath et al 2000;Wildermuth et al 2001). In NPR1-dependent SA signaling, SA binds to NPR1, stimulating its movement to the nucleus where it dimerizes with the TGA2 transcription factor in the presence of copper ions (Kinkema et al 2000;Fan & Dong 2002). The complex then binds to the as-1 promoter sequence 5 ′ TGACGT3 ′ , driving target gene expression (Fan & Dong 2002).…”
Section: Introductionmentioning
confidence: 99%
“…NPR1 is an ankyrin-repeat protein that stimulates plant defenses through the SA-dependent pathway by interaction with transcription factors. This interaction is impaired in npr1-1 (nonexpressor of pathogenesis related genes) mutant plants (Cao et al, 1997;Fan and Dong, 2002;Rairdan and Delaney, 2002). JAR1 is involved in the JA adenylation that is apparently required for JA function and the jar1-1 (JA resistant 1) mutation reduces the impact of the jasmonatedependent defense pathway (Staswick et al, 1992(Staswick et al, , 1998(Staswick et al, , 2002, which becomes activated upon interaction with G. cichoracearum (Zimmerli et al, 2004), making jar1-1 plants useful to reveal responses associated with jasmonate-dependent pathway in this susceptible state.…”
mentioning
confidence: 99%